Pathomorphological Alterations of Aggressive Genital and Extra-genital Canine Transmissible Venereal Tumour - Kumar, Amit; Syal, Priyanka; Singh, Inder Pal; Bhardwaz, Anavil; Kumar, Gaurav (Indian Journal of Veterinary Sciences and Biotechnology, 2025)
Transmissible venereal tumor (TVT) is one of the most common  tumors in canines that mainly spread via  mating.  These tumors grow on the external genitalia and  appear like cauliflower growth which can be nodular,  papillary, pedunculated, or multilobulated and may cause  serosanguinous discharge or bleeding from preputial  orifices and genital canal in males and females, respectively  (Panchkhande et al., 2019). It is also referred as venereal  granuloma, canine transmissible venereal sarcoma,  transmissible lymphosarcoma, and sticker tumor of  mesenchymal origin (Saravanan et al., 2015).
Keywords: serosanguinous; bleeding; mesenchymal